The employment of people with special needs within hotels in Dubai. (10th June 2019) - Al Fardan, Alia; Morris, Stephanie
Abstract : Purpose: The purpose of this paper is to identify the challenges and benefits of hiring individuals with special needs in the hospitality industry in Dubai; understand management, colleague and customer perspectives concerning the integration of individuals with special needs in the workforce; emphasize the need for awareness, communication and training when introducing special needs employees to hotel properties in Dubai; recognize laws and policies in respect to introducing the special needs workforce in hotels in Dubai; and classify the requirements needed to facilitate accessibility and integration of special needs employees in the workforce. Design/methodology/approach: Qualitative research was conducted to better comprehend the benefits, challenges, policies/legalities and perceptions developed when considering employment practices of individuals with disabilities. Interviews with HR directors/managers in hotels in Dubai were conducted using a snowball sampling approach. Findings: This study suggests that hotels in Dubai must increase their efforts to accommodate the special needs market through the provision of accessible areas, changes in perceptions and enactment of coherent laws and policies to prepare for the inflow of disabled tourists during Expo 2020. Further, that these efforts can be better accomplished by employment of individuals with special needs. Originality/value: High turnover costs and shortages of labor in the hospitality industry have led to the need for the non-traditional labor force to fill the demand created by the upcoming Expo 2020. As the UAE won the bid for Expo 2020, there has been early construction of hotels to adapt to the increased demand in jobs by and influx of tourists including individuals with disabilities.